Policy instruments for the governance of the social drivers of health data in clinical and research settings: a policy mapping brief - Levites Strekalova, Yulia A.; Wang, Xiangren; Midence, Sara; Quarshie, Alexander (Frontiers in Public Health, 2024)
This paper maps policy instrument use for the social drivers of health (SDoH) data governance in clinical and research settings. In the United States, Centers for Medicare and Medicaid Services (CMS) and National Institutes of Health (NIH) advocate for standardized data capture. Yet, challenges persist, including limited adoption of CMS-issued SDoH risk codes and gaps in reporting SDoH in clinical trial literature. The mapping across clinical and research SDoH reporting emerges as a comprehensive solution that requires policy support. Specifically, the findings presented in this paper support future policy development through regulatory instruments, fiscal incentives, and knowledge exchange. Actionable recommendations for the United States and international contexts include convening interdisciplinary taskforces, developing agency guidelines for process evaluation, and establishing ethical principles for SDoH data use.